Case Report: Stereotactic body radiation treatment for immunotherapy escaped oligometastatic progression in cutaneous melanoma and merkel cell carcinoma - Khaddour, Karam; Zhou, Alice; Butt, Omar; Huang, Jiayi; Ansstas, George (Frontiers in Oncology, 2023)
Oligometastatic progression represents a unique manifestation of tumor immune-escape that can lead to disease progression during treatment with immune checkpoint inhibitor (ICI). Unfortunately, tThe diagnosis and further optimal management of oligometastatic progression through ICI remains unclear. Diagnostic challenges include practical limitations due to the anatomical sites of oligometastatic progression, such as the para-aortic region, where traditional tissue biopsy carries high risk. Here, and circulating-tumor DNA (ctDNA) represents an emerging minimally-invasive strategy to could aid in diagnosis and disease monitoring as a supplement to surveillance imaging.In this report, we describe two cases of one patient with metastatic melanoma and the other with metastatic Merkel cell carcinoma (MCC) who were treated with ICI and later developed localized resistance due to oligometastatic progression. We further highlight our experience using stereotactic body radiation therapy (SBRT) as a salvage approach to treat the oligometastatic progression. We alsoIn addition, we describe the temporal and dynamic relationship of circulating-tumor DNA (ctDNA) prior to, during and after SBRT, which highly suggested the diagnosis without obtaining a histological specimen. Our cases highlight the potential a potential role for SBRT in the management of oligometastatic progression. However, large prospective trials are essential to confirm the utility of this approach.of ctDNA as a supplement to traditional imaging-based approaches to both guide diagnosis and monitor response.